2019
DOI: 10.1542/peds.2019-0419
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Accuracy of Fast MRI Versus CT for Traumatic Brain Injury in Young Children

Abstract: BACKGROUND: Computed tomography (CT) is commonly used for children when there is concern for traumatic brain injury (TBI) and is a significant source of ionizing radiation. Our objective was to determine the feasibility and accuracy of fast MRI (motion-tolerant MRI sequences performed without sedation) in young children. METHODS: In this prospective cohort study, we attempted fast MRI in children ,6 years old who had head CT performed and were seen in the emergency department of a single, level 1 pediatric tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 29 publications
1
75
0
Order By: Relevance
“…Recent studies of scan times for similar qbMRI protocols found that patients reach the MR scanner from the ED within 30 minutes or order placement. 12,15 Our study showed that most qbMRI studies were obtained within ∼75 minutes of ordering, but many in less than 45 minutes. Cerebral edema/contusion reported use of qbMRI is for evaluation of potential CSF shunt failure in patients with hydrocephalus, who average 8.5 CT scans during childhood.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Recent studies of scan times for similar qbMRI protocols found that patients reach the MR scanner from the ED within 30 minutes or order placement. 12,15 Our study showed that most qbMRI studies were obtained within ∼75 minutes of ordering, but many in less than 45 minutes. Cerebral edema/contusion reported use of qbMRI is for evaluation of potential CSF shunt failure in patients with hydrocephalus, who average 8.5 CT scans during childhood.…”
Section: Discussionmentioning
confidence: 82%
“…This study supports a growing literature describing the use of qbMRI for pediatric trauma indications. 15,17,18 However, our study was unique in a number of ways including a higher population of patients with clinically important traumatic brain injuries which is critical to ensure this imaging modality is identifying the patients at highest risk for morbidity and mortality, a primary outcome focused on clinically important traumatic brain injuries, broader age inclusion than past studies, and being a separate research institute and geographically removed from prior studies. One previous study of qbMRI for head trauma in children less than 6 years of age reported a 92.8% sensitivity for traumatic brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited publications reporting abbreviated brain MRI protocols in the ED and none modeling step-wise implementation for the evaluation of children presenting with head injury. 18 Specifics of the abbreviated brain MRI protocol used in this implementation project are provided in Table 2 with reference to the reasoning for sequence selection. To our knowledge, a single prior brain MRI protocol has been published regarding pediatric head injury evaluation in the ED; however, this protocol does not detail the sequences to an extent that we can perform a side-by-side comparison.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, a single prior brain MRI protocol has been published regarding pediatric head injury evaluation in the ED; however, this protocol does not detail the sequences to an extent that we can perform a side-by-side comparison. 18 However, abbreviated MRI implementation has been detailed in other settings and varying pathologies. 3,[29][30][31] Importantly, equipment, personnel, and financial resources for…”
Section: Discussionmentioning
confidence: 99%